New small molecule inhibitors of histone methyl transferase DOT1L with a nitrile as a non-traditional replacement for heavy halogen atoms. Issue 18 (15th September 2016) - Spurr, Sophie S.; Bayle, Elliott D.; Yu, Wenyu; Li, Fengling; Tempel, Wolfram; Vedadi, Masoud; Schapira, Matthieu; Fish, Paul V.
Graphical abstract: Abstract: A number of new nucleoside derivatives are disclosed as inhibitors of DOT1L activity. SARs established that DOT1L inhibition could be achieved through incorporation of polar groups and small heterocycles at the 5-position (5, 6, 12 ) or by the application of alternative nitrogenous bases (18 ). Based on these results, CN-SAH (19 ) was identified as a potent and selective inhibitor of DOT1L activity where the polar 5-nitrile group was shown by crystallography to bind in the hydrophobic pocket of DOT1L. In addition, we show that a polar nitrile group can be used as a non-traditional replacement for heavy halogen atoms.